DEMOKRASI MELAHIRKAN PLURALISME; BAHAYA DALAM TOLERANSI UMAT BERAGAMA - Jhon Afrizal (Lembaga penelitian dan pengabdian kepada masyrakat, 2011)
This article talk about democracy and pluralism relationship with people tolerance gets religion. Tolerances comprehended pluralism mark sense thinking manner, religion, culture, civilization etc.. Pluralism is gone upon on one wish to smooth away truth. Plurasme is looked on as its appearance trigger extreme attitude, radicaal martial on behalf religion, horizontal conflict, and grind on behalf religion. According to clan pluralis, conflict and violence with mengatasnamakan destroyed new religion if each religion no longer look on its the most religion correctness.